2014
DOI: 10.1186/1756-3305-7-413
|View full text |Cite
|
Sign up to set email alerts
|

A pan-Theileria FRET-qPCR survey for Theileria spp. in ruminants from nine provinces of China

Abstract: BackgroundTheileria spp. are tick transmitted protozoa that can infect large and small ruminants causing disease and economic losses. Diagnosis of infections is often challenging, as parasites can be difficult to detect and identify microscopically and serology is unreliable. While there are PCR assays which can identify certain Theileria spp., there is no one PCR that has been designed to identify all recognized species that occur in ruminants and which will greatly simplify the laboratory diagnoses of infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…A previous study reported a high infection rate of T. luwenshuni in ticks by RLB, or in small ruminants via PCR and FRET-qPCR (Niu et al, 2012;Li et al, 2014a;Yang et al, 2014). In our study, T. luwenshuni was mostly prevalent in Linzhou, Henan province, corresponding with a previous study, which reported T. luwenshuni infecting sheep in the same province (Chen et al, 2014b).…”
Section: Discussionsupporting
confidence: 86%
“…A previous study reported a high infection rate of T. luwenshuni in ticks by RLB, or in small ruminants via PCR and FRET-qPCR (Niu et al, 2012;Li et al, 2014a;Yang et al, 2014). In our study, T. luwenshuni was mostly prevalent in Linzhou, Henan province, corresponding with a previous study, which reported T. luwenshuni infecting sheep in the same province (Chen et al, 2014b).…”
Section: Discussionsupporting
confidence: 86%
“…Although stress (transport, pregnancy, lactation) has been widely reported as a disease trigger (Eamens et al, 2013c;Izzo et al, 2010), the inter-and intra-breed susceptibility of cattle to T. orientalis infection has not been extensively investigated. There is however, some suggestion that there may be differential susceptibility of Bos taurus versus Bos indicus breeds (Yang et al, 2014) and that Japanese black cattle (Wagyu) may be less susceptible to disease (Terada et al, 1995). The animals tested in our temporal study were all of a single breed (Ayrshire) and the patterns of genotype switching and disease progression were remarkably similar amongst the majority of animals.…”
Section: Discussionmentioning
confidence: 94%
“…While real-time assays that detect T. orientalis have been developed, most have focused on species-level detection (not discrimination of genotypes) (34), discrimination of different Theileria spp. (43,44), or are only semiquantitative (28). The UIC multiplex qPCR assay developed here was both sensitive and specific for T. orientalis detection compared to cPCR and reliably identified the clinically relevant Ikeda and Chitose genotypes.…”
Section: Discussionmentioning
confidence: 99%